2019
DOI: 10.4274/btdmjb.galenos.2018.20180528093003
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Transversus Abdominal Plane Block is Effective in Multimodal Analgesia for Laparoscopic Sleeve Gastrectomy

Abstract: Amaç: Obezite cerrahisinde, epidural analjezi ve transversus abdominal plan (TAP) blok ile yapılan multimodal ağrı yönetimi postoperatif etkili bir analjezi sağlayarak, opioidlerin kullanım sıklığını azaltır ve opioid kullanımına bağlı oluşan yan etkileri en aza indirir. Fakat obez hastalarda hem epidural hem de TAP bloğunu uygulamak teknik olarak zordur, bazen imkansızdır. TAP bloğunun laparoskopik olarak yapılması bu teknik zorluğa bir çözüm olabilir. Bu çalışmada laparoskopik sleeve gastrektomide laparoskop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
0
1
1
Order By: Relevance
“…In contrast to our results, Tülübaş et al ( 24 ) designed a prospective randomized study in patients who underwent laparoscopic sleeve gastrectomy. The results showed that there was not any significant difference in both groups regarding postoperative opioid consumption.…”
Section: Discussioncontrasting
confidence: 86%
“…In contrast to our results, Tülübaş et al ( 24 ) designed a prospective randomized study in patients who underwent laparoscopic sleeve gastrectomy. The results showed that there was not any significant difference in both groups regarding postoperative opioid consumption.…”
Section: Discussioncontrasting
confidence: 86%
“…Out of 92 potentially relevant citations, 15 randomized studies (5,(23)(24)(25)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)) and 6 non-randomized studies (47)(48)(49)(50)(51)(52) were selected (Fig. 1).…”
Section: Study Characteristicsmentioning
confidence: 99%